Identification of outcomes to inform the development of a core outcome set for surgical innovation: a targeted review of case studies of novel surgical devices. Issue 4 (29th April 2022) - Wilson, Nicholas; Macefield, Rhiannon C; Hoffmann, Christin; Edmondson, Matthew J; Miller, Rachael L; Kirkham, Emily N; Blencowe, Natalie S; McNair, Angus G K; Main, Barry G; Blazeby, Jane M; Avery, Kerry N L; Potter, Shelley
Abstract : Objective: Outcome selection and reporting in studies of novel surgical procedures and devices lacks standardisation, hindering safe and effective evaluation. A core outcome set (COS) to measure and report in all studies of surgical innovation is needed. We explored outcomes in a specific sample of innovative surgical device case studies to identify outcome domains specifically relevant to innovation to inform the development of a COS. Design: A targeted review of 11 purposive selected case studies of innovative surgical devices. Methods: Electronic database searches in PubMed (July 2018) identified publications reporting the introduction and evaluation of each device. Outcomes were extracted and categorised into domains until no new domains were conceptualised. Outcomes specifically relevant to evaluating innovation were further scrutinised. Results: 112 relevant publications were identified, and 5926 outcomes extracted. Heterogeneity in study type, outcome selection and reporting was observed across surgical devices. Categorisation of outcomes was performed for 2689 (45.4%) outcomes into five broad outcome domains. Outcomes considered key to the evaluation of innovation (n=66; 2.5%) were further categorised as surgeon/operator experience (n=40; 1.5%), unanticipated events (n=15, 0.6%) and modifications (n=11; 0.4%). Conclusion: Outcome domains unique to evaluating innovative surgical devices have been identified. Findings have been combined with multiple other data sources relevant to the evaluation of surgical innovation to inform the development of a COS to measure and report in all studies evaluating novel surgical procedures/devices.